| **Giver** | **Post** | **Date** |

| lethanhquyen166 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 14-Mar-2019 |

| kaustavkarmakar | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 07-Mar-2019 |

| tommig | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Mar-2019 |

| adityapanda | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Mar-2019 |

| tuttifrutti453 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Mar-2019 |

| twoface07 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 24-Feb-2019 |

| bhChicago | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 23-Feb-2019 |

| jhunt17 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 19-Feb-2019 |

| meghaa96 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-Jan-2019 |

| cdc63 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Jan-2019 |

| CJFC8A066 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Dec-2018 |

| Suda | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 24-Dec-2018 |

| KingKong1508 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Dec-2018 |

| reshmiravi | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Dec-2018 |

| robertaconte | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 13-Nov-2018 |

| mbanotioncom | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Oct-2018 |

| Moti580 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 21-Oct-2018 |

| ugnean | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 21-Oct-2018 |

| nihar98 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-Sep-2018 |

| Tomcollins | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 21-Sep-2018 |

| Paul89 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 19-Sep-2018 |

| toeiiitp | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Sep-2018 |

| manjot123 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 31-Aug-2018 |

| iwahbs | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 16-Aug-2018 |

| PreethiVishwanathan | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-Aug-2018 |

| KaulMeAnkit | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 08-Aug-2018 |

| jewelmme | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 07-Aug-2018 |

| delta23 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Aug-2018 |

| jschepp | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Aug-2018 |

| davidgyh | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 25-Jul-2018 |